Prediction of Scar Myometrium Thickness and Previous Cesarean Scar Defect Using the Three-Dimensional Vaginal Ultrasound. (5th October 2022) - Shi, Liang; Du, Keke
Abstract : This research aimed to explore the related factors of scar myometrial thickness and scar diverticulum formation and then predict the occurrence of uterine diverticula. 140 patients with cesarean section were selected as the research objects. According to the three-dimensional (3D) vaginal ultrasound echo and the diagnostic criteria of uterine diverticulum, the research objects were divided into a diverticulum group and a control group, with 70 cases in each group. Data such as age, number of cesarean sections, endometrial thickness, uterine position, and diverticulum size was collected, and their relationship with uterine diverticulum was compared and analyzed. The results showed that there were significant differences in menstrual days, cesarean section times, and uterine position between the two groups ( P  < 0.05). The height (9.02 ± 2.97), width (14.02 ± 3.08), and depth (5.14 ± 1.23) of the posterior uterine diverticula in the scar diverticulum group were all greater than the anterior uterine height (6.69 ± 1.36), the width (10.69 ± 2.15), and the depth (3.86 ± 0.69), respectively. The residual myometrium thickness in posterior position of the uterus (2.98 ± 0.75) was < anterior position of uterus (3.43 ± 0.47), and the difference was statistically significant ( P  < 0.05). Multivariate analysis showed that the frequency of cesarean section (1 time, 2 times), uterine position, and abnormal menstruation were independent risk factors in the scar diverticulum group ( P  < 0.05). In conclusion, menstrual abnormalities, the number of cesarean sections (1 time or twice), and the position of the uterus are independent risk factors for the formation of uterine scar diverticula. The deeper the diverticula, the more likely to have menstrual abnormalities, the more prone to diverticulum in patients with posterior uterus, and the deeper the diverticula in patients with 2 dissections.